"\\hat{f}(\\omega)=\\frac{1}{(2\\pi)^{\\frac{n}{2}}}\\int\\limits_{\\mathbb R^n}f(x)e^{-i(x,\\omega)}dx"
"\\hat{f}(\\omega)=\\frac{1}{(2\\pi)^{\\frac{n}{2}}}\\int\\limits_{\\mathbb R^n}x^{\\alpha}e^{-i(x,\\omega)}dx=\\frac{1}{(2\\pi)^{\\frac{n}{2}}}\\int\\limits_{\\mathbb R^n}\\prod\\limits_{k=1}^n x_k^{\\alpha_k}e^{-ix_k\\omega_k}dx="
"=\\prod\\limits_{k=1}^n\\bigl(\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}x_k^{\\alpha_k}e^{-ix_k\\omega_k}dx_k\\bigr)"
Consider "\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}x^{\\alpha}e^{-ix\\omega}dx". Prove by induction that "\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}x^{\\alpha}e^{-ix\\omega}dx=i^{\\alpha}\\sqrt{2\\pi}\\delta^{(\\alpha)}(\\omega)".
Since "\\delta(\\omega)=\\overline{\\delta(\\omega)}" , for "\\alpha=0" we have "\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}e^{-ix\\omega}dx=\\overline{\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}e^{ix\\omega}dx}="
"=\\sqrt{2\\pi}\\cdot\\overline{\\delta(\\omega)}=\\sqrt{2\\pi}\\delta(\\omega)".
Suppose that "\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}x^ke^{-ix\\omega}dx=i^k\\sqrt{2\\pi}\\delta^{(k)}(\\omega)", where "k\\ge 0".
Then "i^{k+1}\\sqrt{2\\pi}\\delta^{(k+1)}(\\omega)=i\\frac{d}{d\\omega}\\bigl(i^k\\sqrt{2\\pi}\\delta^{(k)}(\\omega)\\bigr)". By the induction hypothesis we obtain "i^{k+1}\\sqrt{2\\pi}\\delta^{(k+1)}(\\omega)=i\\frac{d}{d\\omega}\\bigl(\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}x^ke^{-ix\\omega}dx)\\bigr)="
"=\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}ix^k\\frac{de^{-ix\\omega}}{d\\omega}dx=\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}x^{k+1}e^{-ix\\omega}dx"
So we prove this statement for "\\alpha=k+1".
By the principle of mathematical induction we obtain that "\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}x^{\\alpha}e^{-ix\\omega}dx=i^{\\alpha}\\sqrt{2\\pi}\\delta^{(\\alpha)}(\\omega)" for all "\\alpha\\ge 0".
So "\\hat{f}(\\omega)=\\prod\\limits_{k=1}^n\\bigl(\\frac{1}{\\sqrt{2\\pi}}\\int\\limits_{\\mathbb R}x_k^{\\alpha_k}e^{-ix_k\\omega_k}dx_k\\bigr)="
"=\\prod\\limits_{k=1}^n\\bigl(i^{\\alpha_k}\\sqrt{2\\pi}\\delta^{(\\alpha_k)}(\\omega_k)\\bigr)=i^{|\\alpha|}(2\\pi)^\\frac{n}{2}\\prod\\limits_{k=1}^n\\delta^{(\\alpha_k)}(\\omega_k)"
Answer: "i^{|\\alpha|}(2\\pi)^\\frac{n}{2}\\prod\\limits_{k=1}^n\\delta^{(\\alpha_k)}(\\omega_k)"
Comments
Leave a comment